PENGARUH PERILAKU CEO NARSISME DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR OTOMOTIF 2019 – 2021 (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The most important part that will be the handle of the Automotive company is to maximize its financial performance. The most important part to improve and achieve the goals of a company is to improve financial performance. The type of research data used is quantitative data using data that collects samples because it uses the approach explanatory reseach method to analyze and test the relationship to two variables, namely CEO behavior, Company Size being an independent variable and Company Performance being a dependent variable. The subject of this study data is to take a sample population of the automotive sub-sector & its components collected through the company's website and IDX from 2019 to 2021. Company performance is measured by ROE. The behavior of the CEO of Narcissism can be seen and assessed through the annual report of a company by posting photos. While the size of the company is calculated by natural logarithm multiplied by total sales (LnTotalSale). The conclusion was obtained that there is no influence of CEO Narcissism on company performance and Company Size on the Company Performance of the Automotive sub-sector and its components in 2019 – 2021. Keywords: CEO Narcissism, Company Size, Company Performance, Ln(total sales), ROE.